If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24p-60=-4(1-8p)
We move all terms to the left:
24p-60-(-4(1-8p))=0
We add all the numbers together, and all the variables
24p-(-4(-8p+1))-60=0
We calculate terms in parentheses: -(-4(-8p+1)), so:We get rid of parentheses
-4(-8p+1)
We multiply parentheses
32p-4
Back to the equation:
-(32p-4)
24p-32p+4-60=0
We add all the numbers together, and all the variables
-8p-56=0
We move all terms containing p to the left, all other terms to the right
-8p=56
p=56/-8
p=-7
| h(1)+5h(3)=8 | | 16j^2-484=0 | | g-14=-6 | | -13-3j=-19 | | -6x+10x+11+2=-6x+6x+1 | | 5n^2-720=0 | | 2(9m+12)=3(6m+10) | | x/4/5=45 | | X+(2x-18)+90=180 | | t−218=6. | | 6.2x–5=7.9x+3.5 | | 5x-6=-71-6x | | 7(x+4=3x+56 | | 12+w=-5 | | 24s^2-90s+66=0 | | 11(p-3=5(p+3) | | 3-3(x+5)+8x=7+1 | | (9x+63)=99 | | 1/5n-13=-2 | | x+11+28=3x-7+21 | | 8(1x+6)=80 | | -3s-18=6 | | 10k^2-1210=0 | | 18w-13w+w-w=10 | | 16-9b=-11 | | 13x-15x+8=2-24 | | 18k^2+45k-63=0 | | 0=23w-w^2-132 | | -11=-1/6x-3 | | 18-3f=9 | | x+-12=30 | | 15(x+8)+15-14x=-4 |